Human Cytomegalovirus Genome Diversity in Longitudinally Collected Breast Milk Samples - Götting, Jasper; Lazar, Katrin; Suárez, Nicolás M.; Steinbrück, Lars; Rabe, Tabea; Goelz, Rangmar; Schulz, Thomas F.; Davison, Andrew J.; Hamprecht, Klaus; Ganzenmueller, Tina (Frontiers in Cellular and Infection Microbiology, 2021)
Reactivation and shedding of human cytomegalovirus (HCMV) in breast milk during lactation is highly frequent in HCMV-seropositive mothers. This represents a key transmission route for postnatal HCMV infection and can lead to severe disease in preterm neonates. Little is known about HCMV strain composition or longitudinal intrahost viral population dynamics in breast milk from immunocompetent women. We performed HCMV-specific target enrichment and high-throughput sequencing of 38 breast milk samples obtained in Germany between days 10 and 60 postpartum from 15 mothers with HCMV DNA-lactia, and assembled HCMV consensus sequences de novo. The genotype distribution and number of HCMV strains present in each sample were determined by quantifying genotype-specific sequence motifs in 12 hypervariable viral genes, revealing a wide range of genotypes (82/109) for these genes in the cohort and a unique, longitudinally stable strain composition in each mother. Reactivation of up to three distinct HCMV strains was detected in 8/15 of mothers, indicating that a representative subset of the woman’s HCMV reservoir might be locally reactivated early during lactation. As described previously, nucleotide diversity of samples with multiple strains was much higher than that of samples with single strains. Breast milk as a main source of postnatal mother-to-infant transmission may serve as a repository for viral diversity and thus play an essential role in the natural epidemiology of HCMV.